Panmalarial Immunochromatographic Test May Help in Detection of Rare Species of Malaria - Rahman, Md Arifur; Husain, Md Anwar; Chowdhury, Mahabubur Rahman; Das, Kanti Priyo (Journal of Chittagong Medical College Teachers’ Association, 2016)
We detected a case of Plasmodium malariae in Chittagong, Bangladesh, using traditional microscopy and pan malarial Immunochromatographic Test (ICT). The person was an adult male, presented clinically as severe malaria. Blood slide examination by microscopy and pan malarial ICT revealed the case as Plasmodium malariae infection. The patient presented as severe malaria case for which he was hospitalized and recovered after seven days of quinine treatment. JCMCTA 2016 ; 27 (1) : 59 - 60